Reproductive Hormone Profiles of Malaysian Mahseer (Tor Tambroides Bleeker) in Captivity - Syukri Ismail, Muhammad Fadhil (2010)
Wild matured mahseer consisting of 29 males and 23 females were caught alive from Lipis River (N 4.2349°, E 101.989°), Pahang and with average weight of 0.680.23kg and 0.950.36kg, respectively. The mahseer were placed into a 404.69-m2 earthen pond located at Aquaculture Extension Centre Perlok, Pahang. The annual gonad hormonal profile was investigated from November 2007 to November 2008 using enzyme-linked immunosorbent assay (ELISA) technique. Blood were extracted from the caudal vein monthly and separated by centrifugation to obtain plasma samples. The 17ß-estradiol (E2), testosterone (T) and 11-keto-testosterone (11KT) were measured. Gonads were sampled during March, June and September 2008 when the female mahseer were able to released matured eggs using hand-stripping technique. The gonads were processed using histological method and stained with heamatoxylin and eosin was to observe the gonad development and maturity under light microscope. Highest T level of 0.2220.016 ng/ml and 0.8840.014 ng/ml were recorded in females and males, respectively. The 11KT showed several peaks and highest value was monitored at 0.7030.018 ng/ml in November 2008. The female mahseer E2 initially was at 1.480.16ng/ml and increased significantly (P<0.05) to 1.530.39 ng/ml on November 2008. The concentrations of E2 in the female and 11KT in the male are highly correlated (r=0.86). The presence of both sexes in the same environment may stimulate spermatogenesis and oogenesis. Changes of plasma level in gonadal hormones were correlated with the ovarian and testes development. The present experiment showed significant positive correlation between T and E2 suggesting the role of T as precursor to E2 in the female mahseer. The ovaries were laden with six oocyte stages observed in the entire samples. Late oocyte stages (stage 5 and stage 6) were mostly located at the periphery of posterior gonad, while early stages (stage 1 and stage 2) were located in the center anterior part of the ovaries. All the testes samples showed highest occurrence of spermatozoa compared to spermatocytes or spermatids indicating the fish readiness for spawning. Changes in the hormonal levels are directly related with the testis and oocytes development. Environmental parameters measured such as water, ambient temperatures and dissolved oxygen were within the required levels and almost similar to water quality parameters in the nearby rivers where wild mahseer found. Rainfall data did not illustrate seasonal pattern with the highest value at 13.4mm in December 2007 and lowest at 2.1mm in June 2008. Dissolved oxygen levels averaged 7.4 mg/l throughout the experimental periods. This experiment indicates that mahseer is an asynchronize and multiple spawner. Seasonal changes may have little influence on the breeding pattern of mahseer since it was kept inside an earthen pond that provide suitable condition for the entire year for mahseer to reproduce. The information generated from this study is important for the breeding and conservation programs of the Malaysian mahseer.